Kiss of the rose princess. Volume 9 - Shouoto, Aya, 1977- (VIZ Media, LLC, 2016)
"Anise Yamamoto has been told that if she ever removes the rose choker given to her by her father, a terrible punishment will befall her. Unfortunately she loses that choker when a bat-like being falls from the sky and hits her. Anise is granted four cards representing four knights whom she can summon with a kiss. But now that she has these gorgeous men at her beck and call, what exactly is her quest?! The identity of the Silver Rose is revealed, and Anise learns that her father has been captured by the Society. In order to rescue him, Anise must confront her true enemy...and choose her fate!"--Amazon.